2022
DOI: 10.1186/s11658-022-00317-9
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA let-7 and viral infections: focus on mechanisms of action

Abstract: MicroRNAs (miRNAs) are fundamental post-transcriptional modulators of several critical cellular processes, a number of which are involved in host defense mechanisms. In particular, miRNA let-7 functions as an essential regulator of the function and differentiation of both innate and adaptive immune cells. Let-7 is involved in several human diseases, including cancer and viral infections. Several viral infections have found ways to dysregulate the expression of miRNAs. Extracellular vesicles (EV) are membrane-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 335 publications
0
45
0
Order By: Relevance
“…MicroRNAs (miRNAs) are small (20–23 nts) and non-coding RNA molecules that negatively influence gene expression by binding to mRNAs and thereby promoting degradation of the target mRNA or blocking its translation into protein ( 19 , 68 79 ).…”
Section: Biogenesis and Function Of Micrornas And Their Roles In Prog...mentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs (miRNAs) are small (20–23 nts) and non-coding RNA molecules that negatively influence gene expression by binding to mRNAs and thereby promoting degradation of the target mRNA or blocking its translation into protein ( 19 , 68 79 ).…”
Section: Biogenesis and Function Of Micrornas And Their Roles In Prog...mentioning
confidence: 99%
“…Recent studies have demonstrated that numerous miRNAs can strongly affect the expression of pro- and anti-apoptotic genes, oncogenes, ER stress- and/or necroptosis-related genes ( 20 , 103 ). Aberrations involving miRNAs implicated in apoptosis or necroptosis could also impact physiological conditions and promote disease, including carcinogenesis and infection diseases ( 19 , 104 106 ). Numerous studies have demonstrated that miRNAs usually target multiple mRNAs and they could act as so-called apopto-miRs, oncomiR or tumor suppressor miRNAs in different cancers.…”
Section: Biogenesis and Function Of Micrornas And Their Roles In Prog...mentioning
confidence: 99%
“…An important aspect of virus–host relation during SARS-CoV-2 infection and COVID-19 course is the role of miRNAs. This issue has been a subject of recent reviews [ 132 , 133 ]. One of the first known major modes of action of the virus on the host cell is sequestering of the host miRNAs [ 134 ].…”
Section: Final Remarksmentioning
confidence: 99%
“…miRNAs are a major class of conserved short noncoding RNAs with crucial biological functions in the regulation of a third of the whole genome at the posttranslational level [ 68 ]. miRNAs exert their roles by increasing messenger RNA degradation or by blocking messenger RNA translation [ 69 ].…”
Section: Introductionmentioning
confidence: 99%